Where is the naso-temporal asymmetry? Motion processing. - Braddick, O (1996)
Strabismic (cross-eyed) humans and animals show an imbalance between opposite directions of eye movement. Both midbrain and cortical origins for this asymmetry have been proposed, but there is no sign of it in the main motion-processing area of visual cortex.